Efektifitas Program Rehabilitasi Fisioterapi dalam Mempercepat Pemulihan Cedera Lutut pada Atlet Sepak Bola - Rezki Amalia Nurshal; Sherly Mutiara (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
The rehabilitation program through physiotherapy has proven effective in accelerating the recovery of knee injuries in soccer athletes by employing a structured approach that includes pain reduction, mobility enhancement, and muscle strengthening. Case studies and research indicate that a combination of interventions such as cryotherapy, Transcutaneous Electrical Nerve Stimulation (TENS), range of motion (ROM) exercises, and muscle strengthening leads to significant improvements within 3-6 weeks. The primary methods utilized include physical therapy to reduce edema and pain through modalities like cold compresses and electrical stimulation, progressive exercises focusing on flexibility, balance, and strength of the quadriceps-hamstring muscles, as well as a phased rehabilitation approach (acute, restoration, strengthening) tailored to the patient's clinical condition. Research involving 25 patients post-ACL surgery showed an increase in passive flexion ROM of 31.07% and a decrease in swelling by 3.33% after therapy sessions. For soccer athletes, these interventions facilitate a return to optimal movement function within a short timeframe through controlled sport-specific exercises. The study concludes that a comprehensive physiotherapy program significantly accelerates functional recovery and reduces the risk of long-term complications.